An Insight Over Non-Contractual Liability of Public Administration in Albania - Mataj, Rezarta (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2016)
Despite the purpose of protecting the public interest and citizens’ rights, it is impossible for the public administration and its entities to avoid the damages they cause to them. Nowadays, comparing to two previous centuries, it is consolidated the fact that the State is held responsible for the damage caused as in the civil relations between the private parties. In each impairment caused in the civil law, administrative or criminal ones, there should exist some cumulative elements(in common) whose consumption by the subject brings consequences to the injured party. The law which regulates this responsibility thoroughly is the law no. 8510/1999 “On liability of bodies of state administration”. 65 The Article 1 of this law provides that: “The state administration entities are held responsible for the non-contractual property and non-pecuniary damages, which they cause to the physical persons, legal entities, private, local or foreign ones. Non-contractual liability of public administration entities is regulated according to the provisions of this law and the Civil Code of the Republic of Albania.” In this paper, there will be analyzed the criteria of responsibility determined not only by the respective law but even in those criteria which the Civil Code defines about the non-contractual liability, from the Article 608-652. Through this appraisal, it is aimed at bringing into attention to the readers when the non-contractual state liability arises (concretely the public administration) and in addition, when citizens are legitimated to file a sue against these actions in order that the locals and the foreigners are more aware of this constitutional right not that much applicable. Keywords: state liability, public administrative entities, elements of administrative responsibility, Albanian legal framework.